Crisis and opportunity: the impacts of COVID-19 on water advocacy in Ontario, Canada. Issue 3 (3rd July 2022) - Case, Robert; Eady, Allison
ABSTRACT: This article provides results from interviews and a focus group conducted at two different points in time in the first year of the COVID-19 pandemic, which explored impacts of the pandemic and adaptation among water advocacy organizations in southern Ontario, Canada. Our findings show that despite the destabilizing and sometimes devastating impact of COVID-19 on grassroots organizations and their programs, by disrupting business as usual the pandemic also created the conditions for experimentation, innovation, the establishment of new capacities and strategic foci. In this paper, we share descriptive narratives from water activists in our geographic area about how they adapted and innovated their work despite the challenges of the pandemic. Our findings illustrate and add nuance to themes emerging in the literature about the impacts of the pandemic on environmental advocacy groups and other nonprofit organizations, and generate new themes for further exploration.